(untitled) (Dhaka University Journal of Business Studies, 2023)
Small and medium-sized enterprises (SMEs) is a priority sector in developing countries like Bangladesh. 90% of the employed people are involved in small businesses of Bangladesh, which contribute to 25% of GDP. Like the other sector, this industry may take advantage of cost savings and efficient financial management by adopting mobile payment systems. This study is designed to identify and analyze the factors influencing mobile payment systems adoption in small and medium-sized enterprises. Data has been collected from 200 SMEs through stratified sampling technique and analyzed using modified UTAUT model and PLS-SEM technique. It is found that effort expectancy, performance expectancy, social influence, cost, and voluntariness of use have a statistically significant effect on behavioral intention in adopting a mobile payment system. Journal of Business Studies, Vol. XLII, No. 2, August 2021 Page 47-73